"Locus minoris resistentiae" and connective tissue weakness in older women: a case report and literature review on pelvic organ prolapse with inguinal bladder hernia - A. Esber; A. Kopera; M. P. Radosa; I. B. Runnebaum; H. K. Mothes; A. R. Mothes (BMC, 2021)
Abstract Background Conditions such as genital prolapse and hernia are known to be related to connective tissue dysfunction. In this report on cases of the rare simultaneous finding of large genital prolapse and post-prolapse repair female inguinal bladder hernia, we aim to contribute to the discussion of a possible clinical definition of connective tissue weakness, for its clinical assessment and preoperative patient counselling. Case presentation Three cases of medial third-grade (MIII, Aachen classification) inguinal bladder hernia developing or enlarging after successful stage-IV pelvic organ prolapse (POP) repair at a university pelvic floor centre are presented. All patients were aged ≥ 80 years with long-standing postmenopausal status. One patient was followed for 5 years and two patients were followed for 6 months. In all patients, ultrasound revealed that the hernia sac contained the urinary bladder, which had herniated through the inguinal hernia orifice. A literature search revealed only one case report of direct female inguinal bladder hernia and few investigations of the simultaneous occurrence of POP and hernia in general. Conclusion The simultaneous occurrence of inguinal hernia and female POP can lead to bladder herniation following prolapse surgery in the sense of a "locus minoris resistentiae". Clinical examination for simultaneous signs of connective tissue weakness and counselling prior to pelvic reconstructive surgery could help to increase patients' compliance with further surgical treatment for hernia.